18‐2: Assessment of Image Quality in Augmented Reality Displays Using a Computational Model of Target Detectability. Issue 1 (28th June 2022) - Zhao, Chumin; Beams, Ryan; Johnson, Matthew; Badano, Aldo
Abstract : We characterized augmented reality (AR) displays and developed a computational task‐based model to evaluate their image quality. The model enables fast assessment of image quality and evaluation of tradeoffs between display configurations such as display luminance response, uniformity, resolution, and noise. This work supports the development and optimization of AR displays without extensive measurements or resource‐intensive perception studies.